Hands-On G Suite for Administrators Build and Manage Any Business on Top of the Google Cloud Infrastructure. - Anton Dorantes, Cesar (Packt Publishing Ltd, 2019)
Hands-On G Suite for Administrators is a comprehensive hands-on guide to G Suite Administration that will prepare you with all you need to know to become a certified G Suite Administrator, ready to handle all the business scales, from a small office to a large enterprise.